Capital Structure and Corporate Governance: Shaping Company Value through Dividends - Khorita, Siti Arifatul; Widodo, Heri (Indonesian Journal of Public Policy Review, 2024)
Background: The dynamic interplay between corporate financial strategies, particularly capital structure and dividend policies, significantly influences firm value in the manufacturing sector.Knowledge Gap: While previous research has explored the direct relationships between capital structure and firm value, less attention has been paid to the moderating effects of dividend policy, profitability, and Good Corporate Governance (GCG) in this context. Aims: This study aims to assess the moderating roles of dividend policy, profitability, and GCG on the relationship between capital structure and firm value. Results: The findings indicate that dividend policy, profitability, and GCG significantly moderate the relationship between capital structure and firm value, suggesting that firms must balance dividend distribution with their capital structure decisions. Novelty: This research contributes to the existing literature by integrating dividend policy and GCG into the analysis of capital structure's effect on firm value, addressing previously overlooked aspects. Implications: The study underscores the importance of prudent dividend policies and robust corporate governance in enhancing firm value, offering valuable insights for managers and investors aiming to optimize financial performance in the competitive food and beverage manufacturing sector. Highlights : Moderating Effects: Dividend policy, profitability, and GCG significantly moderate the relationship between capital structure and firm value. Financial Balance: Firms must balance dividend distribution with capital structure decisions to enhance overall value. Managerial Insights: The findings provide crucial insights for managers and investors to optimize financial performance in the food and beverage sector. Keywords: capital structure, dividend policy, firm value, profitability, Good Corporate Governance